Mermaid in Pathology from Greek Mythology: A Rare Association with Amelia - Chikkanaganna P. Manjula; Vijay Karthik Pranav; V. Kusuma; Shilpashree Varadaraj (Archives of Medicine and Health Sciences)
Sirenomelia, also known as mermaid syndrome, is a rare congenital anomaly, with an incidence of 1 in 100,000 live births. It is characterized by variable degrees of fusion of the lower limbs and anomalies of the genitourinary system and gastrointestinal system. We report a 24-week fetus with completely fused lower limbs, absent left upper limb, and Potter’s facies. Absent external genitalia, imperforate anus, bilateral renal agenesis, blind intestinal loop, and single umbilical artery were other findings. X-ray imaging confirmed the fused lower limb bones and was typed as sympus apus or sirenomelia, Type VII of the Stocker and Heifetz classification. Caudal hypoperfusion due to the aberrant blood supply and an embryologic insult to the caudal mesoderm along with gestational diabetes play a role. Sirenomelia is not compatible with life in the majority of the cases as there is bilateral renal agenesis. It is a very rare congenital anomaly among the mermaid syndromes, hence requires documentation.